STRATEGI GURU DALAM MENINGKATKAN SIKAP NASIONALISME MELALUI PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DI SMAN 1 NGADIROJO PACITAN - Maya Desi Wijayanti; I Made Suwanda (Universitas Negeri Surabaya (Unesa), 2022)
This study aims to find out the implementation of strategies applied by PPKn SMA Negeri 1 Ngadirojo teachers in improving students' nationalism attitudes through PPKn learning and its obstacles. The type of research used in this study is a type of qualitative research with a descriptive method. Data collection was carried out through observation, in-depth interviews and documentation. The source of the data from this study was obtained from ppkn teachers of SMA Negeri 1 Ngadirojo. The location of the study was conducted at SMA Negeri 1 Ngadirojo, Pacitan Regency. The results showed that the learning strategies carried out by teachers include the preparation of a Learning Implementation Plan with the determination of indicators, objectives, learning models and teaching media. In addition, it also involves students in activities outside the classroom with several conditions. In the implementation of learning, PPKn teachers apply in accordance with the Learning Implementation Design which has previously been designed based on the results of observations in the classroom. Teachers also practice habituation such as singing the song Indonesia Raya before starting the learning process. The teacher evaluates at the end of each lesson, at the time of midterm and the end of the semester. Evaluation is based on daily scores in the form of pop quizzes, midterm exams and end-of-semester exams, while to measure the success of implementing strategies is to look at changes in student attitudes and responses based on achievement indicators. There are several obstacles in implementing the strategy including, class conditions that are not conducive, limited student activities outside the classroom that can be followed, lack of learning concentration, and lack of student enthusiasm. Keywords: strategy, PPKn teachers, nationalism.